Potential therapeutic effects of an ayahuasca-inspired N,N-DMT and harmine formulation: a controlled trial in healthy subjects - Aicher, Helena D.; Mueller, Michael J.; Dornbierer, Dario A.; Suay, Dila; Elsner, Claudius; Wicki, Ilhui; Meling, Daniel; Caflisch, Luzia; Hempe, Alexandra; Steinhart, Camilla; Mueller, Jovin; Von Rotz, Robin; et al. (Frontiers in Psychiatry, 2024)
Background: There is growing scientific evidence for the therapeutic benefits of the Amazonian plantbased psychedelic "ayahuasca" for neuropsychiatric disorders such as depression and anxiety. However, there are certain challenges when incorporating botanical ayahuasca into biomedical research and clinical therapy environments. Formulations inspired by ayahuasca, which contain specific and standardized active components, are a potential remedy. Methods: We investigated subjective acute and persisting effects of a novel formulation containing the reversible monoamine oxidase inhibitor harmine (orodispersible tablet containing 100 mg MAO-I) and N,N-dimethyltryptamine (incremental intranasal dosing of up to 100 mg DMT), compared with two other conditions, namely harmine alone and placebo, in a crossover RCT in 31 healthy male subjects. Results: DMT+harmine, but not harmine alone, induced a psychedelic experience assessed with the 5D-ASC rating scale (global score: F(2,60) = 80.21, p <.001) and acute experience sampling items over time, characterized by psychological insights (PIQ, F(2,58.5) = 28.514, p <.001), emotional breakthroughs (EBI, F(2,60) = 26.509, p <.001), and low scores on the challenging experience questionnaire (CEQ, F(2,60) = 12.84, p <.001). Participants attributed personal and spiritual significance to the experience (GSR) with mainly positive persisting effects (PEQ) at 1-and 4-months follow-up. Acute drug effects correlated positively with persisting effects. We found no changes in trait measures of personality, psychological flexibility, or general well-being, and no increases in psychopathology (SCL-90-R) were reported. Discussion & Conclusion: Our results suggest that the experience induced by the standardized DMT+harmine formulation induces a phenomenologically rich psychedelic experience, demonstrates good psychological safety and tolerability, is well tolerated, and induces beneficial psychological processes that could possibly support psychotherapy. Further studies are required to investigate the psychotherapeutic potential in patients.